Begonia medeiroii (Begoniaceae), a new species endemic to Santa Catarina, southern Brazil - Funez, Luís Adriano; Jaramillo, Julio Cesar; Drechsler-Santos, Elisandro Ricardo (Phytotaxa, 2019)
We describe here Begonia medeiroii, a narrow endemic species from the Atlantic Rainforest. The conservation status of this species was assessed as critically endangered according to IUCN criteria. This species resembles to B. catharinensis and B. hirtella in some characteristics, differing among other features due the presence of adventitious vegetative buds on the adaxial surface of the leaves.